Micro-CT scan optimisation for mechanical loading of tibia with titanium tibial tray: A digital volume correlation zero strain error analysis. (October 2022) - Wearne, Lauren S.; Rapagna, Sophie; Taylor, Mark; Perilli, Egon
Abstract: Primary stability of press-fit tibial trays is achieved by introducing an interference fit between bone and implant. The internal cancellous bone strains induced during this process and during loading have yet to be quantified experimentally. Advancements in large-gantry micro-CT imaging and digital volume correlation (DVC) allow quantification of such strains. However, before undertaking such a test, experimental requirements and DVC performance need to be examined, particularly considering the presence of a large orthopaedic implant (tibial tray). The aim of this study was to assess the DVC zero-strain accuracy (mean absolute error: MAER) and precision (standard deviation of error: SDER) on a cadaveric human tibia implanted with a titanium press-fit tray across four plausible scanning configurations, using a cabinet micro-CT system (Nikon XT H 225 ST). These varied in rotation step and resulting scanning time (106 min vs. 66 min), presence or absence of a 2 mm-thick aluminium cylinder for mechanical testing, and X-ray tube voltage (150 kVp vs. 215 kVp). One proximal tibia was implanted and micro-CT scanned (42 μm/pixel), with repeated scanning and specimen repositioning in between. DVC (DaVis, LaVision, direct correlation) was performed on nine cubic volumes of interest (VOIs: 13.4 mm-side) and across the entire proximal tibia. Strain errors were comparable across the four scanning configurations and sufficiently low for assessing bone within its elastic region in VOIs (MAER=223-540 με; SDER=88-261 με) and at organ level (MAER=536 με; SDER=473 με). Whilst the investigated experimental conditions, including a large titanium implant, present added complexity for DVC analysis, scans of sufficient quality can be achieved, reaching a compromise between the DVC requirements and the wanted application. The approach used for choosing the X-ray source settings considering the transmitted X-ray signal intensity and source power, is also discussed. Graphical abstract: Image 1 Highlights: Four plausible scan configurations show minor differences in DVC accuracy±precision. Presence of titanium tray adds complexity, but sufficient quality scans were achieved. Zero-strain errors across the entire tibia (organ level) were 536±473 με. Zero-strain errors of examined scan configurations permit elastic analysis of bone. Analysis of elastic deformation of tibia with titanium implant is possible.